LncRNA KCNQ1OT1 Secreted by Tumor Cell-Derived Exosomes Mediates Immune Escape in Colorectal Cancer by Regulating PD-L1 Ubiquitination via MiR-30a-5p/USP22 - Xian, Di; Niu, Liangbo; Zeng, Jie; Wang, Lei (Frontiers in Cell and Developmental Biology, 2021)
Background: This study tried to explore the mechanism of lncRNA KCNQ1OT1 in tumor immune escape. Methods: Microarray analysis is used to screen the differentially expressed lncRNA and miRNA in normal tissues and tumor tissues. RT-qPCR was used to quantify KCNQ1OT1, miR-30a-5p, USP22 and PD-L1. The interactive relationship between KCNQ1OT1 and miR-30a-5p was verified using dual-luciferase reporter gene assay and RIP assay. CCK-8, clone formation, wound healing and apoptosis are used to detect the occurrence of tumor cells after different treatments. Protein half-life and ubiquitination detection are used to study the influence of USP22 on PD-L1 ubiquitination. BALB/c mice and BALB/c nude mice are used to detect the effects of different treatments on tumor growth and immune escape in vivo. Results: The expression of lncRNA KCNQ1OT1 in tumor tissues and tumor cell-derived exosomes was significantly increased. The tumor-promoting effect of LncRNA KCNQ1OT1 was through the autocrine effect of tumor cell-derived exosomes, which mediates the miR-30a-5p/USP22 pathway to regulate the ubiquitination of PD-L1 and inhibits CD8 + T cell response, thereby promoting CRC development occurs. Conclusions: Tumor cell-derived exosomes KCNQ1OT1 could regulates PD-L1 ubiquitination through miR-30a-5p/USP22 to promote colorectal cancer immune escape.